Superoxide dismutase overexpression protects dopaminergic neurons in a Drosophila model of Parkinson's disease. - Botella, J.A.; Bayersdorfer, F.; Schneuwly, S. (Neurobiology of Disease, 2008)
Parkinson's disease (PD) is characterized by the progressive loss of dopaminergic neurons in the substantia nigra pars compacta. Some of the inherited forms of the disease are caused by mutations in the alpha-synuclein gene and the triplication of its locus. Oxidative stress has been proposed as a central mechanism for the progression of the disease although its relation with alpha-synuclein toxicity remains obscure. Targeted expression of human alpha-synuclein has been effectively used to recreate the pathology of PD in Drosophila melanogaster and it has been proved an excellent tool for the study of testable hypothesis in relation to the disease. We show that dopaminergic neurons are specifically sensitive to hyperoxia induced oxidative stress and that mutant forms of alpha-synuclein show an enhanced toxicity under these conditions suggesting synergic interactions. In addition, the co-expression of Cu/Zn superoxid dismutase protects against the dopaminergic neuronal loss induced by mutant alpha-synuclein overexpression thus identifying oxidative stress as an important causative factor in the pathology of autosomal-dominant Parkinsonism.